Written communication by public servants: A case study on responding with the right words amid challenging contexts at the Housing Authority of Baltimore City. (2nd January 2021) - Dolamore, Stephanie
ABSTRACT: Teaching workplace communication is vitally important as we expect public servants to have the skills to draft, review, and revise written communication materials. Less explicitly demanded, and more often implicitly expected, we assume public servants know how to respond to individuals with empathy while also meeting technical obligations, such as adhering to conventional formats and meeting regulations imposed by administrative or statutory law. The compounding nature of these requirements provides a challenging context for public servants to write responsive and appropriate messages. Using a second-person narrative to heighten empathic skill development, this case study explores how a public servant at the Housing Authority of Baltimore City navigates writing formal responses to members of the community amid difficult circumstances. This case study presents an opportunity for public servants to learn about combining interpersonal and technical skills while communicating on the job.